The United Nations Global Compact: Engaging Implicit and Explicit CSR for Global Governance - Brown, Jill A. (Journal of business ethics, 2018)
This article analyzes the United Nations Global Compact (UNGC) under the conceptual framework of explicit versus implicit corporate social responsibility (CSR) to better understand the operational and governance challenges behind this voluntary global initiative. Using institutional logics theory, we show how the UNGC is a practice that embodies seemingly competing logics. We suggest mechanisms to facilitate the interplay of implicit/explicit CSR and the co-existence of logics that might allow the UNGC to move forward while addressing its critics. We argue that failure to conceptualize the UNGC as a combination of explicit and implicit CSR leaves the UNGC subject to criticism that might be better directed toward organizations that fail to practice explicit CSR. While viewing the UNGC through an integrated CSR framework may not immediately reconcile its critics and proponents, combining elements of both may provide opportunities to posit collaborative solutions to improve the quality, outcome, and legitimacy of UNGC initiatives.